Birds, beasts and burials : a study of the human-animal relationship in Romano-British St. Albans - Hill, Brittany Elayne, (Archaeopress Roman archaeology ;, 2017)
'Birds, Beasts and Burials' examines human-animal relationships as found in the mortuary record within the area of Verulamium that is now situated in the modern town of St. Albans.